The BFG - Dahl, Roald; Blake, Quentin (New York : Puffin Books, 2007)
Kidsnatched from her orphanage by a BFG (Big Friendly Giant), who spends his life blowing happy dreams to children, Sophie concocts with him a plan to save the world from nine other man-gobbling cannybull giants.
Elem. School Library Collection
School Library Journal
Wilson's Children
Book Links (A.L.A.), July 2006
Booklist, September 1996
Elem. School Library Collection, June 2000
Keywords: Giants -- Juvenile fiction; Orphans -- Juvenile fiction; Giants -- Fiction; Orphans -- Fiction; Giants -- Fiction; Orphans -- Fiction